2020
DOI: 10.1017/s0269964820000285
|View full text |Cite
|
Sign up to set email alerts
|

ON RELIABILITY FUNCTION OF A K-OUT-OF-N SYSTEM WITH GENERAL REPAIR TIME DISTRIBUTION

Abstract: The reliability study of k-out-of-n systems is of interest both from theoretical and practical points of view. Applications of such models can be seen in many real-world phenomena, including telecommunication, transmission, transportation, manufacturing, and services. A probabilistic study of a real-world k-out-of-n system often helps to develop an optimal strategy for maintaining high system-level reliability. There are many investigations devoted to the reliability-centric analysis of such systems. We consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 28 publications
(40 reference statements)
0
9
0
Order By: Relevance
“…The dominant variables can be further studied using other types of SA if the first moments [70], or the pdf shapes [90,91], or the importance of the components [92] are not explicitly known, as is often the case in engineering practice. Conversely, non-influential inputs can be fixed at any value of their domain without affecting Pf, usually close to the mean value.…”
Section: Discussionmentioning
confidence: 99%
“…The dominant variables can be further studied using other types of SA if the first moments [70], or the pdf shapes [90,91], or the importance of the components [92] are not explicitly known, as is often the case in engineering practice. Conversely, non-influential inputs can be fixed at any value of their domain without affecting Pf, usually close to the mean value.…”
Section: Discussionmentioning
confidence: 99%
“…The bibliography (on publications about these systems) is extensive (see Trivedi [1], Chakravarthy et al [2] and the bibliography therein). For a brief overview of further investigations on this topic, please see, for example, [3]. An overview of recent publications on k-out-of-n multi-state systems can be found in [4].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore it is fundamentally important to study the sensitivity of the system reliability indicators with respect to the shape of their unit lifetime distributions. Research in this direction can be found in a series of our papers, references to which one can find in chapter 9 of [34], as well as in [3]. For an overview of the recent research methods for queuing and reliability systems, one can find it in [35].…”
Section: Introductionmentioning
confidence: 99%
“…The literature on such studies is vast (see for example Trivedi [12], Chakravarthy et al [13] and the bibliography therein). The bibliography of later studies can be found in, e.g., in [14]. Most of these investigations deal with the systems under assumptions about components' Poisson failure flow and exponential distribution of their repair time.…”
Section: Introductionmentioning
confidence: 99%
“…In the series of our previous works, the bibliography of which one can find for example in [14], for an investigation of a renewable k-out-of-n system with the Poisson flow of its components' failures and their arbitrarily distributed repair times, the socalled Markovization method was used. The method consists of the introduction of supplementary variables that allows describing the system behavior by a two-dimensional Markov process.…”
Section: Introductionmentioning
confidence: 99%